Pengaruh Co-Branding Dear Me Beauty X KFC Terhadap Keputusan Pembelian - Qorie Isnaen Fadilla; Jamiati KN (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Co-branding is a strategy that can be used by two companies that blend to attract consumer attention and obtain a wider target market. So the purpose of this study is to determine whether or not there is an influence of co-branding carried out by Dear Me Beauty with KFC on purchasing decisions and to find out how much influence results from the collaboration carried out. The theories used in this study are co-branding theories, including adequate brand awareness, strong enough brands, profitable, unique mergers, positive consumer assessments and positive consumer responses, and purchasing decision theories, which include problem recognition, information search, alternative evaluation, purchase decisions, and post-purchase behavior. This study uses a quantitative research methodology with a survey method. The population in this study were followers of the @dearmebeauty Instagram account. The data collection technique was carried out by distributing questionnaires to 75 respondents according to predetermined characteristics and taking samples using simple random sampling. The results of respondents' answers to variable (X) were classified as high answering agree with an average value of 3.45, and the variable (Y) was classified as high answering agree with an average value of 3.47. The results of the simple linear regression test conducted show that Dear Me Beauty co-branding with KFC has a strong or high influence on purchasing decisions of 62.6%, while the remaining 37.4% is influenced by other factors. The results of the hypothesis test show that H0 is rejected and H1 is accepted, which means that there is a significant influence between co-branding and purchasing decisions.